Evapotranspiração e coeficientes de cultivo (KC) da cana-de-açúcar irrigada por gotejamento subsuperficial - Gonçalves, Fabricio Mota (2010)
Sugar cane is one of the crops with the highest level of water consumption, with a high evapotranspiration demand throughout most of its cycle. Knowledge of the sugar cane water demand, the time that irrigation should be applied, and how to irrigate the crop are becoming increasingly important for the sustainable development of irrigated sugar cane cultivation, especially in areas of low water availability, as it is the case in northea stern Brazil. The experiment was carried out at the Curu Experimental Field (property of the Embrapa Tropical Agroindustry), located in the Curu-Paraipaba Irrig ation Project, city of Paraipaba-CE (3 ° 29 '20''S, 39 ° 9' 45''W and elevation 30m), in order to determine the evapotrans piration and crop coefficients (Kc) of sugarcane (Saccharum L. officinarium), subsurface drip-irrigated. It was used the SP 6949 sugar cane variety, planted in a spacing of 1.8 m between double rows and 0.4 m between rows within the double row. As to t he irrigation, we used one lateral water line for each double row, buried at a depth of 0.15 m, w ith self-compensating drip emitters, with a flow rate of 1 L h-1, spaced 0.5 m on the water line. The crop was irrigated daily and there were three fertigations per week. The irrigation de pth was periodically adjusted, keeping the soil water potential between -8 kPa to -20 kPa. The crop evapotranspiration (ETc) was determined using a wei ghing lysimeter with a surface area of 2.25 m 2. The reference evapotranspiration (ETo) was estimated by the FAO Penman-Monteith method. The durations of the phenological stages of cane sugar were estimated through analysis of soil cover, with the use of digital images. Durations of 31, 49, 237 and 118 days were observed, respectively for initial, crop development, mid-season and late season stages. The yields achieved within and outside the lysimeter were respectively 144.4 and 108.8 t ha -1 . The total ETc observed during the cycle of the sugar cane was 1074.1 m m, with maximum values of 6.6 mm d-1 during the mid-season stage. Observed Kc values for initial, mid-season and late season stages were respectively 0.23, 1 .03 and 0.50. In the crop development stage, the relationship between Kc and the (crop) soil cover was represented with good accuracy by a negative quadratic model.